2013
DOI: 10.1128/jb.00794-13
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes Multidrug Resistance Transporters and Cyclic Di-AMP, Which Contribute to Type I Interferon Induction, Play a Role in Cell Wall Stress

Abstract: The intracellular bacterial pathogen Listeria monocytogenes activates a robust type I interferon response upon infection. This response is partially dependent on the multidrug resistance (MDR) transporter MdrM and relies on cyclic-di-AMP (c-di-AMP) secretion, yet the functions of MdrM and cyclic-di-AMP that lead to this response are unknown. Here we report that it is not MdrM alone but a cohort of MDR transporters that together contribute to type I interferon induction during infection. In a search for a physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
65
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 56 publications
1
65
0
Order By: Relevance
“…To directly evaluate the interaction between the domains of PgpH and c-di-AMP, we used a differential radial action of ligand assay (DRACALA), which tests for protein binding with radiolabeled nucleotides (25). These binding experiments indicated that the ED domain and MBP alone did not interact with 32 P-c-di-AMP, whereas the MBP-HD domain construct exhibited clear binding (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To directly evaluate the interaction between the domains of PgpH and c-di-AMP, we used a differential radial action of ligand assay (DRACALA), which tests for protein binding with radiolabeled nucleotides (25). These binding experiments indicated that the ED domain and MBP alone did not interact with 32 P-c-di-AMP, whereas the MBP-HD domain construct exhibited clear binding (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate binding specificity, we conducted competition assays, in which unlabeled nucleotides were added in excess to disrupt 32 P-c-di-AMP interaction with MBP-HD protein. Among the nucleotides tested, only 5′-pApA and c-di-GMP diminished radiolabeled c-di-AMP binding, although much less than unlabeled c-di-AMP (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While c-di-AMP has been found to regulate many important functions in bacteria, including cell wall stress and peptidoglycan homeostasis (11)(12)(13)(14)(15), antibiotic resistance (16)(17)(18), biofilm formation (19), growth and metabolism (20)(21)(22)(23), and DNA damage response (24,25), it can also modulate leukocyte activation. For example, c-di-AMP secretion into the macrophage cytosol induces a robust type I interferon (IFN [IFN-␤]) response during intracellular bacterial infections, including those caused by Listeria monocytogenes (26,27), Chlamydia trachomatis (28), and Mycobacterium spp.…”
mentioning
confidence: 99%
“…Further studies have identified cyclic di-AMP (c-di-AMP) as a substrate of MdrM and as the ligand that triggers the innate immune system to express type I interferons (46,50). While immune cells rapidly sense this cyclic dinucleotide as a signal for bacterial invasion, within the bacteria it was shown to play a regulatory role in cell wall stress responses and homeostasis (49,51).…”
mentioning
confidence: 99%
“…We have previously shown that activation of the type I interferon response by L. monocytogenes relies on the expression of a set of bacterial multidrug-resistant transporters-MdrM, MdrT, MdrA, and MdrC-that together are responsible for most of the response in murine macrophages (48,49). Among these transporters, MdrM was found to be most critical, as deletion of its gene alone led to ϳ70% reduction in IFN-␤ induction compared to that induced by wild-type bacteria.…”
mentioning
confidence: 99%